PENGELOLAN AIR LIMBAH DOMESTIK DKI JAKARTA DI TINJAU DARI PENGELOLAAN AIR LIMBAH DOMESTIK DI SINGAPURA - Soefianto Soetono (Halu Oleo University, 2024)
This study aims to identify the problems of managing waste water into clean water in the Special Capital Region of Jakarta from the perspective of Water Resources Law. Using a normative juridical approach, namely a legal research method carried out by examining library materials or secondary data. The results of the research show that waste water management in the State of Singapore can be said to be quite successful and can be an example to be adopted and implemented in DKI Jakarta as part of the form of handling in order to realize the mandate of Article 33 Paragraph (3) of the 1945 Constitution, namely distributed social justice in responding to legal reality regarding the purpose of water as a social asset and capital asset so as to close the gap in privatization of water by the private sector.